Comprehensive Review of Wind Energy in Malaysia: Past, Present, and Future Research Trends - Noman F.M.; Alkawsi G.A.; Abbas D.; Alkahtani A.A.; Tiong S.K.; Ekanayake J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cost effectiveness; Green manufacturing; Wind; Carbon emissions; Contributing factor; Electric energies; Green technology; Spatial mapping; Wind energy research; Wind prediction; Wind speed and directions; Wind power